Sub‐phenotyping Metabolic Disorders Using Body Composition: An Individualized, Nonparametric Approach Utilizing Large Data Sets. Issue 7 (16th May 2019) - Linge, Jennifer; Whitcher, Brandon; Borga, Magnus; Dahlqvist Leinhard, Olof
Abstract : Objective: This study performed individual‐centric, data‐driven calculations of propensity for coronary heart disease (CHD) and type 2 diabetes (T2D), utilizing magnetic resonance imaging‐acquired body composition measurements, for sub‐phenotyping of obesity and nonalcoholic fatty liver disease (NAFLD). Methods: A total of 10, 019 participants from the UK Biobank imaging substudy were included and analyzed for visceral and abdominal subcutaneous adipose tissue, muscle fat infiltration, and liver fat. An adaption of the k‐nearest neighbors algorithm was applied to the imaging variable space to calculate individualized CHD and T2D propensity and explore metabolic sub‐phenotyping within obesity and NAFLD. Results: The ranges of CHD and T2D propensity for the whole cohort were 1.3% to 58.0% and 0.6% to 42.0%, respectively. The diagnostic performance, area under the receiver operating characteristic curve (95% CI), using disease propensities for CHD and T2D detection was 0.75 (0.73‐0.77) and 0.79 (0.77‐0.81). Exploring individualized disease propensity, CHD phenotypes, T2D phenotypes, comorbid phenotypes, and metabolically healthy phenotypes were found within obesity and NAFLD. Conclusions: The adaptive k‐nearest neighbors algorithm allowed an individual‐centric assessment of each individual's metabolic phenotype moving beyond discrete categorizations of body composition. Within obesity and NAFLD, this may help in identifying which comorbidities a patient may develop and consequently enable optimization of treatment.